Factors Towards EV Adoption Among Malaysian M40 and T20 Income Groups - Atan @ Yaakub, Siti Anisah; Rahman, Muhammad Syahmi (Research in Management of Technology and Business, 2022)
According to Global EV Outlook 2020 report by the International Energy Agency (IEA), the transportation sector accounts for around one-fourth of total global greenhouse gas emissions and are expected to rise from 23 percent to 50 percent by 2030. This significant contribution of transportation sector towards environmental pollution, accelerate the speed of initiatives in reducing carbon emissions and mitigating the dependency on fossil fuels in the sector. Inevitably, energy-efficient transportation innovations such as EVs are seen as one of the most effective ways to counter the problems. EVs were launched in Malaysia as one of the solutions to minimize fossil fuel dependency and carbon emissions caused by the transportation sectors, motivated by energy efficiency and emission concerns. Based on EV current prices, only Malaysian middle-and-high income consumers can afford to buy an EV. Therefore, the aim of this study to know the intention of M40 and T20 income groups to use EVs and to determine the relationship between studied factors and intention to use EVs. This research was using quantitative method and online Google Form survey questionnaire was used to collect the data from respondents. A total of 154 questionnaires had been returned and analyzed using SPSS. Descriptive analysis, reliability test, normality test, and Spearman correlation test were run on the data to answer research objectives. This study found that Malaysian middle-and-high income groups have high intention to adopt EV and they will possibly be buying EV in the future. This study also showed that variables such as demographic, financial benefits, infrastructure readiness, government intervention, performance attributes have significant positive relationship with the intention to adopt EVs among respondents. The findings of this study can provide some insights to EV stakeholders on formulating strategies towards promoting EV adoption in Malaysia.